The presence of bluetongue virus serotype 8 RNA in Belgian cattle since 2008. - Garigliany, M; Ilse De Leeuw; Kleijnen, D; Frank Vandenbussche; Callens, J; Van Loo, H; Lebrun, M; Saulmont, M; Desmecht, D; Kris De Clercq (Transbound Emerg Dis, 2011)
After a short winter break, bluetongue virus serotype 8 was responsible in 2007 for a large-scale epidemic among ruminant populations in Western Europe. Little is known about the mechanisms allowing the virus to survive winter conditions. A yearly mass vaccination of cattle and sheep started in spring 2008, which was recognized as successful in terms of clinical protection, but occult circulation of the bluetongue virus has not been adequately addressed. We studied the carriage of bluetongue RNA in the spleen of cattle in the vector-free period and the circulation of bluetongue virus in cattle populations in Belgium since the introduction of vaccination programmes. Overall, the results presented here show evidence for the long-term carriage of bluetongue virus RNA in the spleen of cattle and demonstrated a low but significant circulation and transplacental transmission of bluetongue virus in Belgian cattle in 2009, with apparent disappearance in 2010.
Keywords: Animals; Belgium; Bluetongue; Bluetongue virus; Carrier State; Cattle; Cattle Diseases; Reverse Transcriptase Polymerase Chain Reaction; RNA, Viral; Spleen; Time Factors; Viral Vaccines